A Study of Causal Factors, Knowledge Management, and Technology Adoption for Corporate Social Responsibility in the Electric Vehicle Industry toward Sustainability - Davis, Murray; Changkomchome, Thanawan; Yongtinnung, Punyanut; Tanskul, Kawissara; Sukkri, Mesawadi (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study focuses on personal factors, causal factors, and knowledge management, and their influences on the adoption of technology for corporate social responsibility (CSR) within the electric vehicle (EV) industry toward sustainability. The sample group consists of 400 EV users in Thailand, with data collected via questionnaires. Statistical analyses included frequency, percentage, analysis of observed variables, measurement models, and structural equation modeling (SEM) using the Partial Least Square (PLS) method.The results indicate that personal factors significantly affect causal factors in knowledge management, which in turn influence technology adoption for sustainable EV business operations. Both measurement and structural equation models confirmed the consistency of the research framework with empirical data across all indicators. These findings assist businesses in identifying strengths and weaknesses, leading to the formulation of appropriate policies and strategies to create added value for both businesses and society in the long term.